KONFLIK KELUARGA DALAM NOVEL LILIN KARYA SANIYYAH PUTRI (KAJIAN PSIKOLOGI ABRAHAM MASLOW) - fuji alfina; Anshari Anshari; Nensilianti Nensilianti (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
Family Conflict in the Novel Lilin by Saniyyah Putri (Abraham Maslow's Psychological Study) This study aims to describe the relationship between family conflict and the non-fulfillment of the hierarchy of human needs contained in the novel being analyzed. This type of research is qualitative. The research data are in the form of words, sentences, and paragraphs that reveal the contents of the story in the novel. The data source for this research is the novel Lilin by Saniyyah Putri, which was published in 2020. The approach used is the psychological study of Abraham Maslow. The results of this study indicate that there are two types of conflict found: conflicts according to Abraham Maslow's theory and conflicts that occur between members. This study also found three basic needs that were not met, namely physiological needs, safety needs, and needs for love and affection. Besides that, there were also two basic needs that were barely met, namely the need for self-esteem and the need for self-actualization, causing conflict. in Elena's family.